Mineral resources grade 11 STEM road map for high school - Johnson, Carla C., 1969-; Walton, Janet B., 1968-; Peters-Burton, Erin E. (New York, NY : Routledge, 2022)
What if you could challenge your eleventh graders to come up with a design solution for developing, managing, and utilizing mineral resources? With this volume in the STEM Road Map Curriculum Series, you can! Mineral Resources outlines a journey that will steer your students toward authentic problem solving while grounding them in integrated STEM disciplines. Like the other volumes in the series, this book is designed to meet the growing need to infuse real-world learning into K-12 classrooms. This interdisciplinary, three-lesson module uses project- and problem-based learning to help students develop an in-depth understanding of mineral resources by researching the utility and impact of particular mineral resources on society. Working in teams, students will locate quantitative and qualitative data on mineral resources and discern the reliability of the information, then use their data to write an opinion article and develop a website to convince readers of the effectiveness of a particular design solution for developing, managing, and utilizing mineral resources. To support this goal, students will do the following: Explain how mineral resources are located and used in various ways in society. Explain why mineral resources are important to society. Critically evaluate quantitative and qualitative data about mineral resources. Write an opinion article demonstrating their knowledge about competing design solutions for extracting mineral resources. The STEM Road Map Curriculum Series is anchored in the Next Generation Science Standards, the Common Core State Standards, and the Framework for 21st Century Learning. In-depth and flexible, Mineral Resources can be used as a whole unit or in part to meet the needs of districts, schools, and teachers who are charting a course toward an integrated STEM approach.
Keywords: Mines and mineral resources; Eleventh grade (Education); EDUCATION / Teaching Methods & Materials / Science & Technology; EDUCATION / Teaching Methods & Materials / Mathematics; EDUCATION / Curricula